2004
DOI: 10.1590/s0100-84042004000200011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrate and ammonium on the growth and protein concentration of Microcystis viridis Lemmermann (Cyanobacteria)

Abstract: -(Effect of nitrate and ammonium on the growth and protein concentration of Microcystis viridis Lemmermann (Cyanobacteria)). Cyanobacteria are a very important group in aquatic systems, particularly in eutrophic waters. Therefore studies about their success in the environment are essential. Many hypotheses have tried to explain the dominance of Cyanobacteria, and several emphasized the importance of various nitrogen sources for the success of the group. In this study, we measured the effect of ammonium and nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 23 publications
3
23
0
1
Order By: Relevance
“…The cells of Microcystis spp. were able to utilize nitrate as a nitrogen source to form amino acids, chlorophyll and other organic compounds [5]. The decrease of nitrate in the medium macrophyte comprising the combination of F. globulosa and V. zizanoides without the addition of Microcystis in the fifteenth day reached about 99.94%, whereas the macrophyte combination in the medium with the addition of Microcystis was approximately 99.84%.…”
Section: Resultsmentioning
confidence: 97%
“…The cells of Microcystis spp. were able to utilize nitrate as a nitrogen source to form amino acids, chlorophyll and other organic compounds [5]. The decrease of nitrate in the medium macrophyte comprising the combination of F. globulosa and V. zizanoides without the addition of Microcystis in the fifteenth day reached about 99.94%, whereas the macrophyte combination in the medium with the addition of Microcystis was approximately 99.84%.…”
Section: Resultsmentioning
confidence: 97%
“…These authors predicted dominance by eukaryotes when NO 3 -is the major N source, and cyanobacteria dominance would be strongly connected to NH 4 + availability, since this phylum seems to be able to grow faster in this nitrogen source (e.g. Herrero et al 2001;Rückert & Giani 2004). As observed in Marola Lake, other studies have demonstrated that NH 4 + may be the major DIN source in some eutrophic ecosystems (e.g.…”
Section: Discussionmentioning
confidence: 93%
“…It is indicated that under nutrient limitation stress condition there is a negative correlation between growth rate and lipid content (Roleda et al, 2013). Inoculation of SH4 medium with seed cells grown in N8 put cells in an environment with low nitrogen but in form of ammonium that was easier to uptake (Von Ruckert and Giani, 2004). This situation increased biomass production because of the change in metabolism and improved specific growth rate from 0.0058/h to 0.0083/h.…”
Section: Resultsmentioning
confidence: 99%